Hygienic Disposal of Children's Stools Practices Among Women of Children With Diarrhoea in Sub-Saharan Africa - Mainprice Akuoko Essuman; Rebecca Peniel Storph; Bright Opoku Ahinkorah; Eugene Budu; Sanni Yaya (SAGE Publishing, 2023)
Background: Diarrhoea stools contain infectious agents and pose a public health threat to children and members of the entire family when exposed to them. Therefore, their hygienic disposal is essential. Empirical data are needed to stir the needed public health interventions to encourage or enforce proper disposal practices to curb associated clinical issues. This study assessed the prevalence and correlates of hygienic stool disposal practices by mothers of children with diarrhoea in sub-Saharan Africa (SSA). Methods: The Demographic and Health Surveys (DHS) data of 16 sub-Saharan African countries from 2015 to 2021 involving 22 590 mother-child pairs were analysed. Multilevel binary logistic analysis was conducted to assess the individual- and household-level factors associated with the hygienic disposal of stool practices by mothers of children with diarrhoea. The results were presented using adjusted odds ratios (AOR) and 95% confidence intervals (CI) at a statistical significance of P  < .05. Results: The overall prevalence of hygienic disposal of children's stools among women of children with diarrhoea was 49.01% (95% CI: 48.40-49.62) and ranged from 15.70% in Liberia to 86.6% in Rwanda. The practice of hygienic disposal of stools of children with diarrhoea was likely to increase among mothers who are working (AOR: 1.19; 95% CI: 1.09-1.30), those with partners with primary level of education (AOR: 1.18; 95% CI: 1.06-1.31), Muslims (AOR: 1.69; 95% CI: 1.49-1.91) and widowed/divorced (AOR: 8.94, 95% CI: 3.55-22.53). Again, mothers in the richer (AOR: 1.23; 95% CI: 1.08-1.39) wealth index had increased odds of disposing of stools hygienically compared to those in the poorest wealth index. Women who were 20 years and above, to who belonged to Traditional Religions (AOR: 0.57; 95% CI: 0.43-0.74), and those with unimproved sources of water (AOR: 0.89; 95% CI: 0.82-0.98) and toilet facilities (AOR: 0.63; 95% CI: 0.58-0.69) were less likely to dispose of child's diarrhoea stool hygienically than their counterparts. Conclusion: The study reveals that the unhygienic disposal of the stool of children with diarrhoea is prevalent in SSA and requires a concerted effort to curb it. Sanitation practices such as educating mothers about hygienic disposal of children's stool and improving water and sanitation facilities are crucial in lowering the high prevalence of unhygienic disposal of the diarrhoeic stool of children. Additional country-level research is needed to assess children's defecation behaviours and the disposal of diarrhoeic stools using different methodologies.